PENGARUH E-SERVICE QUALITY DAN BRAND IMAGE TERHADAP REPURCHASE INTENTION MELALUI E-SATISFACTION (Studi Kasus pada Mahasiswa FISIP UNDIP yang Pernah Melakukan Pembelian di OLX.co.id) - Kresno Yudho Wicaksono Manopo; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2019)
The online buying and selling service sector is one of the service sectors needed by modern society, the needs of modern society for online buying and selling services must be considered. Currently in Indonesia there is an online buying and selling service that allows consumers not to come to a store directly to buy a product. OLX is one of the means of buying and selling online that is of interest to Indonesian consumers, but there are still problems in OLX causing consumers to feel hesitant to use, as evidenced by the decrease in the number of OLX consumer transactions and complaints. This type of research is explanatory research, using a questionnaire as a data collection method. The research method used is the Non Probability Sampling technique with the sampling technique using Purposive Sampling. The number of samples determined by 100 respondents from undergraduate students in the Faculty of Social and Political Sciences of Diponegoro University was chosen based on consideration. The study used Partial Least Square analysis techniques, which were estimated by the WarpPLS 3.0 program. The results of the analysis with WarpPLS explained that the results of the direct influence test on the research model showed positive and significant results. The indirect effect test on the research model also showed positive and significant results. Researchers gave advice to OLX to improve the quality of service both from the seller's side and OLX itself so that consumers feel comfortable, then improve the order delivery system which is thought to be long, and more promotions to the media that are close to potential consumers.